The Rice Peptide Transporter OsNPF7.3 Is Induced by Organic Nitrogen, and Contributes to Nitrogen Allocation and Grain Yield - Fang, Zhongming; Bai, Genxiang; Huang, Weiting; Wang, Zhixin; Wang, Xuelu; Zhang, Mingyong (Frontiers in Plant Science, 2017)
Nitrogen use efficiency is important for the development of sustainable agriculture. Plants have different transporters to facilitate nitrogen uptake and internal distribution. This study demonstrates that the peptide transporter OsNPF7.3 enhances nitrogen allocation and increases grain yield in rice. OsNPF7.3 is a member of the nitrate transporter 1/peptide transporter family (NPF) and is localized in the vacuolar membrane. Its expression is higher in the lateral roots and stems. Its transcripts concentrate in the vascular bundle and significantly regulated by organic nitrogen sources. The RNAi lines of OsNPF7.3 affect plant growth and cause amino acids to accumulate in leaf sheaths and decrease in the leaf blades. At later stages of reproductive growth, nitrogen degradation accelerates in the leaves of plants over-expressing OsNPF7.3 and the nitrogen is translocated to grains. The tiller numbers, panicles per plant, filled grain numbers per panicle, and grain nitrogen content of the OsNPF7.3 over-expressing plant were more than that of wide type. The elevated gene expression in OsNPF7.3 could enhance nitrogen utilization efficiency in rice paddy.